Protective Effect of Melatonin Against Polymicrobial Sepsis Is Mediated by the Anti-bacterial Effect of Neutrophils - Xu, Li; Zhang, Wei; Kwak, Minseok; Zhang, LiJun; Lee, Peter C. W.; Jin, Jun-O (Frontiers in Immunology, 2019)
Sepsis is an infection- or toxin-mediated systemic inflammatory syndrome. Previous studies have shown that melatonin, the primary hormone produced by the pineal gland, attenuates the effect ofpolymicrobial infection-mediated septic shock in animals. However, the mechanism of the anti-septic effect of melatonin during polymicrobial infection has not been well studied. In this study, we investigated how melatonin protects mice from polymicrobial sepsis. Melatonin treatment inhibited peripheral tissue inflammation and tissue damage in a cecal ligation puncture (CLP)-induced polymicrobial sepsis model, consequently reducing the mortality of the mice. We found that macrophages and neutrophils expressed melatonin receptors. Upon depletion of neutrophils, melatonin-induced protection against polymicrobial infection failed in the mice, but melatonin treatment in macrophage-depleted mice attenuated the mice mortality resulting from polymicrobial sepsis. Moreover, melatonin treatment promoted the development of the neutrophil extracellular trap (NET), which contributed to anti-bacterial activity during polymicrobial infection, whereas the phagocytic activities of neutrophils were inhibited by melatonin. The data from this study support previously unexplained antiseptic effects of melatonin during a polymicrobial infection and could be potentially useful for human patients with sepsis.